Facilitating intelligent media space collaboration via RASCAL: The reflectively adaptive synchronous coordination architectural framework. - Robbins, Robert Wayne. (University of Ottawa (Canada), 2001)
The increasing connectivity across domestic, commercial and recreational domains has lead to convergence not only in terms of technology, but also in terms of utility and expectation: people wish to work, play and interact together regardless of technological differences and without the need to continuously adapt to the idiosyncrasies of their collaborative tools. This desire to work together across diversity in location, technology, focus and intent creates the need to facilitate systems that are inherently malleable and that not only emphasize system function, but also how the system behaves. Combined with the proliferation and integration of multimedia technologies, these aspects have provided the impetus to realize collaborative multimedia systems that can meet the diverse and abstract needs of the collaborative process as its participants, scenarios and technologies change and evolve. To do so, this work proposes a reflectively adaptive software engineering framework and support architecture to facilitate the construction of collaborative media spaces. Known as RASCAL, the Reflectively Adaptive Synchronous Coordination Architectural framework explicitly separates behaviour from functionality through the use of a meta-level architecture. Such an approach enables the potential development of intelligent, self-adaptive collaborative systems that can modify their internal construction to meet varying user expectations, behavioural patterns and physical resource constraints. The general framework and supporting communication topology are presented along with an overview of a conceptual prototype called MSpace. Potential usage media-based scenarios ranging from business to artistic venues are explored along with a general evaluation of the system in terms of its reflective nature as well as its potential as a collaborative environment. Future work and additional research opportunities conclude with the observation that RASCAL's underlying essence of reflective adaptivity offers the most potential to meet the evolving needs, expectations and complexity that will someday make such an approach to system sign not a luxury but a necessity.
Keywords: Computer Science.